Teaching mathematics through a cultural lens: Allowing students to resonate the academic content - Angga Hidayat (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
Indonesia is a country of diversity, with a variety of different cultures incorporated into the national identity. With a great range of cultural groups existing in Indonesia, it is essential for teachers to implement a cultural approach in their mathematics classes to ensure that students from all backgrounds have the opportunity to learn and understand the academic content. This article intends to explore the topics of multicultural education in mathematics classrooms. It has been found in the pieces of literature available that an appreciation of cultural dissimilarities can be beneficial and should be seen as an advantage rather than a shortcoming. To accommodate this peculiarity, there are strategies that can be utilized such as funds of knowledge, ethnomathematics, and also storytelling within mathematics lessons. These strategies grant teachers multiple methods of preserving culture while at the same time teaching mathematics effectively and efficiently.